2010
DOI: 10.1016/j.immuni.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Sensing of Environmental Stimuli by Follicular Dendritic Cells Promotes Immunoglobulin A Generation in the Gut

Abstract: In the Peyer's patches (PPs), germinal centers (GCs) are chronically induced by bacteria and are the major sites for generation of gut immunoglobulin A (IgA) immune responses. Whether follicular dendritic cells (FDCs) within the GCs directly contribute to the IgA production in PPs is unknown. We showed here that direct stimulation of FDCs by bacterial products and retinoic acid synergistically enhanced the expression of the chemokine CXCL13, the survival factor BAFF, and molecules that facilitate the secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
247
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(262 citation statements)
references
References 52 publications
9
247
2
4
Order By: Relevance
“…We and others previously reported that absence of vitamin A causes a se- vere reduction of IgA cells in the gut because of impaired germinal center formation in Peyer's patches, defective class switching of B2 cells from IgM to IgA, and impaired homing of IgA plasmablasts from the Peyer's patches to the gut lamina propria (15)(16)(17). However, many IgA plasma cells can be generated from the peritoneal B1 cells by germinal center-independent pathways (3,18).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We and others previously reported that absence of vitamin A causes a se- vere reduction of IgA cells in the gut because of impaired germinal center formation in Peyer's patches, defective class switching of B2 cells from IgM to IgA, and impaired homing of IgA plasmablasts from the Peyer's patches to the gut lamina propria (15)(16)(17). However, many IgA plasma cells can be generated from the peritoneal B1 cells by germinal center-independent pathways (3,18).…”
Section: Resultsmentioning
confidence: 93%
“…All mice were bred and maintained as previously described (15). VAD mice were prepared as described (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells have recently been isolated and studied in vitro (72,73). The implications of adjuvant binding to the FDC have previously not been analyzed (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…FDCs are known to express TLR4 and can be activated upon challenge with LPS, thus promoting accessory activity and enhancing IgG responses (74). Upon activation, FDC increase expression of adhesion molecules (VCAM-1, ICAM-1, and mucosal addressin cell adhesion molecule-1), CXCL13, BAFF, and cytokines (IL-1b, IL-5, IL-10 and IL-15) and upregulate TLR4 expression (26,72,73). Whether CTA1-DD activated FDC in a TLR-independent fashion and which promoting effects it had leading to upregulated GC reactions will be studied in detail in future experiments.…”
Section: Discussionmentioning
confidence: 99%